KONDISI KADAR ESTROGEN DALAM DARAH PADA SAPI PERANAKAN ONGOLE (PO) DAN PERANAKAN SIMMENTAL (SIMPO) DI PETERNAKAN RAKYAT - , DIMAS AKBAR SANTOSA, drh. Erif Maha Nugraha Setyawan, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are many influence of genetic affacts on reproductive performance and productivity levels and simPO PO cows. High temperatures causes LH and FSH decrease so that not only result of the hormone levels are decrease but also estrogen levels in the blood, so it is necessary to doing research, that is to know the levels of estrogen in the blood of PO cattle and simPO in different areas. There are 6 heads of cows, which consists of 3 cows PO and 3 cows simPO used in this research. The method of the research started when the cattle estrus and perrektal exploration of PO simPO, then continue by blood sampling via venous coccigea. Blood sampling used by a syringe 5 ml of eacl cow in the data then it transferred to a plastic tube with a lid size 1 ml, next doing separation of the supernatant by centrifugation at a speed of 4000 rpm for 10 min and stored at -20Â°C. Then the hormone estrogen was analysis by ELISA, blood serum was sent to the Department of Physiology Laboratory Veterinary Gadjah Mada University. The result of descriptive analysis by comparing of the results of measurements of the average levels of estrogen in the blood and the literature that is know that the results of the examination was normal range. Based on the statistical analysis showed that the levels of estrogen cows and cows PO simPO on difference (>0,05). This research shows the levels of estrogen in the blood of cattle and PO simPO cattle not significantly different.